The relationship between physical activity and career decision-making self-efficacy in Chinese college students: the mediating roles of self-control and social anxiety - Yuan Fang; Tingting Xu; Maosheng Ye; Changquan Li (Frontiers in Psychology)
ObjectivesEnhancing career decision-making self-efficacy is an effective approach to improving university graduates' employment quality and speed. This study aims to explore the relationships among physical activity, career decision-making self-efficacy, self-control, and social anxiety to provide new perspectives and directions for enhancing university students' career decision-making self-efficacy.MethodsWithin the framework of this research endeavor, a cohort of 1,955 university students (N = 1,955) from 14 universities distributed throughout China was surveyed. The initial data was entered and stored by means of Microsoft Excel. Subsequently, SPSS version 26.0 was employed to execute a comprehensive set of statistical analyses on the data, including descriptive statistics, a normality test, a reliability test, an exploratory factor analysis (aimed at addressing common method bias), a correlation test, and a regression analysis. In the present study, a structural equation model was formulated via the utilization of AMOS 24.0 software, and the Bootstrap approach was implemented. A total of 5,000 samples were randomly drawn for the purpose of validating the research hypotheses, with the determination being based on whether the 95% confidence interval encompassed the value of 0.Results(1) Physical activity was found to positively predict career decision-making self-efficacy, as evidenced by (Estimate = 0.590, p < 0.001). (2) Self-control was demonstrated to play a mediating role in the connection between physical activity and career decision-making self-efficacy, with the effect indicated by (Estimate = 0.075, 95%CI(0.042, 0.113)]. (3) Social anxiety was likewise shown to assume a mediating role within the relationship between physical activity and career decision-making self-efficacy, as manifested by [Estimate = 0.009, 95%CI(0.002, 0.020)]. (4) A chain mediating effect was observed between physical activity and career decision-making self-efficacy for the combination of self-control and social anxiety, with [Estimate = 0.032, 95%CI(0.008, 0.057)].ConclusionThese findings provided significant theoretical support for physical activity as an effective means to enhance university students' career decision-making self-efficacy and offered references for designing sports activity programs. Furthermore, this study offered new perspectives and directions for understanding and enhancing university students' career decision-making self-efficacy.